Recently Discovered Iron Anchors from Tamil Nadu, East Coast of India. (28th December 2020) - Tripati, Sila; Prabaharan, N.; Behera, Rudra Prasad
In maritime archaeological studies, anchors made of stone, wood, or metal have played a significant role in shipping, not only acted as a proxy during the period of their use but also suggesting maritime connections with other countries. Anchors of different types have discovered all over the world which used in the vessels engaged in carrying cargo, passengers as well as warships. Iron anchors were introduced in India by the European rulers, and later on, were manufactured in different parts of India. Like the stone anchors, different types of iron anchors have been recorded during onshore explorations as well as underwater sites with and without shipwreck remain along the Indian coast. In recent past, coastal explorations along Tamil Nadu coast brought to light two iron anchors at Tuticorin harbour while other two anchors displayed at the Government Museum, Egmore, Chennai. Both the iron anchors of Tuticorin harbour belong to Trotman type. In contrast, the iron anchors of the Government Museum, Egmore, belong to Old plan Long shanked Anchor (Admiralty Long Shanked) and Admiralty pattern anchor. This paper details a comprehensive study of these iron anchors and a comparative survey of the iron anchors of Tamil Nadu as well as India.